Managing Surged Furrow Irrigation - Lee, Teang Shui; Tajomavo, J. (Universiti Putra Malaysia Press, 1996)
The behaviour of the infiltration process in an irrigation system is the most important feature that must be determined. Knowledge of soil infiltration, as it is a dominant physical process in surface irrigation, is crucial to the successful implementation of the scheme. This cannot be over-emphasized in surface systems, especially in furrow systems. This paper describes the infiltration behaviour of a furrow irrigation system under the surge flow regime. Infiltration behaviour over the various runs was studied, Suggestions for the implementation of such a management-oriented irrigation practice are discussed. The infiltration characteristics over the various flows are given.